Robust Collaterals Are Independently Associated With Excellent Recanalization in Patients With Large Vessel Occlusion Causing Acute Ischemic Stroke - Vivek Yedavalli; Manisha Koneru; Meisam Hoseinyazdi; Cynthia Greene; Karen Copeland; Risheng Xu; Licia Luna; Justin Caplan; Adam A. Dmytriw; Adrien Guenego; Jeremy Heit; Gregory Albers; et al. (Stroke: Vascular and Interventional Neurology, 2024)
Background In patients with acute ischemic stroke secondary to large vessel occlusion, achieving modified Thrombolysis in Cerebral Infarction (mTICI) 2c/3 (excellent recanalization) over mTICI 2b is associated with improved functional outcomes. We aimed to determine pretreatment and interventional parameters that are independently associated with mTICI 2c/3 over 2b reperfusion in patients who underwent technically successful mechanical thrombectomy. Methods In this retrospective study, consecutive patients with acute ischemic stroke with anterior circulation large vessel occlusion achieving mTICI 2b/2c/3 recanalization after mechanical thrombectomy were included. We evaluated the association between pretreatment clinical, imaging, and interventional parameters in patients who achieved mTICI 2c/3 versus 2b using multivariate logistic regressions. Results From May 11, 2019 to October 9, 2022, 149 consecutive patients met our inclusion criteria (median 70 years old [interquartile range 65–78.5], 57.7% female). Adjusted multivariate regression analyses showed that patients with excellent recanalization had lower admission National Institutes of Health Stroke Scale scores (adjusted odds ratio [aOR], 0.93; P=0.036), were less likely to have a history of diabetes (aOR, 0.42; P=0.050) and prior stroke (aOR, 0.27; P=0.007), had a cerebral blood volume index ≥0.7 (aOR, 3.75; P=0.007), and were more likely to achieve excellent recanalization with aspiration alone (aOR, 2.89; P=0.012). A multivariate logistic regression model comprising these independent factors predicted mTICI 2c/3 with an area under the curve 0.79 (95% CI, 0.68–0.86; P<0.001), sensitivity of 94%, and specificity of 41%. Conclusion Robust collateral status defined by cerebral blood volume index ≥0.7 on pretreatment computed tomography perfusion, absence of prior stroke, and absence of diabetes are independently associated with excellent recanalization in patients with successfully recanalized acute ischemic stroke‐large vessel occlusion. Our findings highlight the prognostic implications of robust collateral status and modifiable risk factors that may influence collateral status for maximizing the likelihood of excellent recanalization.